Pengaruh Kualitas Produk, Harga, dan Promosi terhadap Loyalitas Pelanggan Pabrik Tahu Wak Gentong di Desa Hessa Perlompongan - Widia Putri Utami; Tengku Syarifah (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The tofu industry is one of the important sectors in supporting the local economy in Indonesia. Increasing business competition, fluctuating soybean prices, and changing consumer behavior require business actors to maintain customer loyalty through product quality, pricing strategies, and promotional activities. This study aimed to analyze the influence of product quality, price, and promotion on customer loyalty at Wak Gentong Tofu Factory in Hessa Perlompongan Village. This research used a quantitative approach with a descriptive nature based on Sugiyono (2023). The study was conducted at Wak Gentong Tofu Factory from January to April 2026. The population consisted of 32 employees, all of whom were selected as the sample using a saturated sampling technique. Research data were collected through the distribution of Likert-scale questionnaires and analyzed using IBM SPSS version 27. The data analysis technique employed multiple linear regression analysis. The results showed that product quality and promotion had a positive and significant effect on customer loyalty, while price had a positive but insignificant effect. Simultaneously, product quality, price, and promotion significantly influenced customer loyalty. The coefficient of determination indicated that 67.4% of customer loyalty could be explained by the three independent variables examined in this study.